Optimization of Inotropic Support in Victims with Polytrauma and Acute Heart Failure - N. A. Karpun; V. V. Moroz; A. N. Afonin (Общая реаниматология)
Objective: to evaluate the impact of ultrasound-guided nerve imaging on the efficiency and safety of supraclavicular brachial plexus block. Subjects and methods. Sixty-five patients underwent supraclavicular brachial plexus block. According to the method of nerve identification, all the patients were allocated to one of two groups: 1) Kulenkampff’s block, by identifying the nerves by a nerve stimulator (n=30); 2) supraclavicular block, by identifying the nerves by ultrasound scanning (n=35). Anesthesia was carried out with a local anesthetic solution containing 20 ml of 2% lidocaine and 10 ml of 0.5% bupivacaine (a total of 30 ml). Results. There is evidence for the high efficiency (97.1%) of ultrasound-guided nerve imaging and its safety (no multiple attempts to verify nerves and complications) as compared to the Kulenkampff supraclavicular block using neurostimulation to identify the plexus (p<0.05). Conclusion. The authors’ modified ultrasound-guided imaging in performing the brachial plexus block helps define nerve localization and observe the placement of a needle against the anatomic structures as it is advanced. Local anesthetic spread observed by ultrasound scanning confirms the precise location of the needle tip. Key words: ultrasound-guided nerve imaging, brachial plexus, efficiency of anesthesia, complication, supra-clavicular approach.